Early intervention for mild cognitive impairment: a randomised controlled trial. Issue 7 (29th March 2009) - Kinsella, G J; Mullaly, E; Rand, E; Ong, B; Burton, C; Price, S; Phillips, M; Storey, E
Abstract : Background: Positive effects are reported for memory training for healthy older adults, and yet there is limited information about the benefit of cognitive intervention for older adults with increasing memory difficulties—mild cognitive impairment. Objective: To investigate the usefulness of an early cognitive intervention for the memory difficulties experienced by people with amnestic mild cognitive impairment. Methods: Using a randomised control design, 52 participants with amnestic mild cognitive impairment and their family partners were randomly assigned to a cognitive intervention (memory rehabilitation group) or waitlist (control group). Participants were assessed on primary measures of everyday memory (prospective memory) and memory strategies at 2 weeks' and 4 months' follow-up; secondary measures of contentment with memory and the family participants' knowledge of memory strategies were also assessed. Results: Everyday memory, measured by performance on prospective memory tasks, significantly improved following intervention, although self-appraisal of everyday memory did not demonstrate a similar intervention effect. Knowledge and use of memory strategies also significantly increased following intervention. Furthermore, family knowledge of memory strategies increased following intervention. There was a strong trend towards improvement in contentment with memory immediately following intervention, but this effect was not significant. Conclusions: Early intervention for memory difficulties in amnestic mild cognitive impairment, using cognitive rehabilitation in compensatory strategies, can assist in minimising everyday memory failures as evaluated by performance on prospective memory tasks and knowledge of memory strategies.